2021
DOI: 10.1111/ijfs.15072
|View full text |Cite
|
Sign up to set email alerts
|

A potential of banana flower and pseudo‐stem as novel ingredients rich in phenolic compounds

Abstract: Banana by-products as novel ingredients S. Ram ırez-Bolaños et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This level was 1.5-3 times higher than that recorded in the pulp [11]. These confer a wide range of biological and pharmacological properties with potential as antimutagenic, antiviral antithrombotic, hepatoprotective agents, as well as a food additive and signaling molecules because of strong natural antioxidant properties [12,13]. Many fruit peels' phenolic compounds have now been studied [14].…”
Section: Introductionmentioning
confidence: 94%
“…This level was 1.5-3 times higher than that recorded in the pulp [11]. These confer a wide range of biological and pharmacological properties with potential as antimutagenic, antiviral antithrombotic, hepatoprotective agents, as well as a food additive and signaling molecules because of strong natural antioxidant properties [12,13]. Many fruit peels' phenolic compounds have now been studied [14].…”
Section: Introductionmentioning
confidence: 94%
“…The flowers of Tilia tomentosa contained 66.820 3,4‐dihydroxybenzoic acid, 29.39 myricetin, 21.421 rutin, 12.334 ferulic acid, 10.383 4‐hydroxybenzaldehyde, 3.542 4‐hydroxybenzoic acid, 0.232 gallic acid, 1.824 caffeic acid, and 3.683 mg/kg kaempferol (Kıvrak et al, 2017). Ramírez‐Bolanos et al (2021) reported that dried banana flower and dried banana pseudostem may have the potential to be used as food ingredients due to the phenolic profile of dried banana flower and its byproducts. Solarte et al (2022) determined that a deficiency of myricetin derivatives was also detected in Tibouchina urvilleana .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been observed that the interest of consumers in the herbs and nutritional supplements has increased due to the lack of side effects and low costs of natural antioxidant sources compared to synthetic drugs (Buřičová & Réblová, 2008; Bubueanu et al, 2015). Both dried banana flower and pseudo‐stem showed an interesting nutritional composition, like proteins in the case of pseudo‐stem and proteins and fatty acids in the flower (Ramírez‐Bolanos et al, 2021). Polyphenolic compounds with antioxidant properties are widely found in both edible and inedible plants and they have many applications in the food, cosmetic, and pharmaceutical industries (Shaiban et al, 2006; Arabshahi‐Delouee & Urooj, 2007; Akyüz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given this current trend of clean-label foods, extensive research has been conducted on the identification and characterization of plant-based antioxidant substances [ 73 , 74 , 75 , 76 , 77 ]. As a consequence, studies on the application of these substances as replacers of conventional synthetic antioxidants in meat and meat products have increased in recent years, as shown in Figure 1 .…”
Section: Compounds/ingredients From Plants With Antioxidant Actionmentioning
confidence: 99%